First Report of Long-Billed Plover Charadrius placidus from Maharashtra, Central India - Morey, Kiran; Abhang, Ninad; Wadatkar, J. S.; Wagh, G. A.; Kadu, G. S. (Journal of the Bombay Natural History Society (JBNHS), 2014)
No abstract.